Neutrophil extracellular traps and peptidylarginine deiminase 4-mediated inflammasome activation link diabetes to cardiorenal injury and heart failure: translational science : diabetes and metabolic disorders - Schommer, Nicolas; Gendron, Nicolas; Krauel, Krystin; Van Bruggen, Stijn; Jarrot, Pierre-André; Maier, Alexander; Chan, William; Langer, Harald; Dürschmied, Daniel; Westermann, Dirk; Klingel, Karin; Wagner, Denisa D; et al. (European heart journal, 2025)
Diabetes is associated with increased risk of cardiovascular and renal disease. This study investigated the role of peptidylarginine deiminase 4 (PAD4), neutrophil extracellular traps (NETs), and inflammasome activation in diabetic cardiomyopathy (DCM) and kidney disease (DKD).Endomyocardial biopsies (EMB) from heart failure (HF) patients (n = 20) with or without diabetes were stained for NETs. Wild-type (WT) and PAD4⁻/⁻ mice were subjected to streptozotocin (STZ)-induced diabetes and cardiac function, blood glucose, body weight, and exercise tolerance were assessed longitudinally. NETosis and ASC specks were evaluated in mouse and human neutrophils. Cardiac and renal fibrosis was assessed by Sirius Red/Fast Green staining. Confocal microscopy, ELISA, and flow cytometry were used to quantify NETs, IL-1β, von Willebrand factor (VWF), cytokine transforming growth factor beta-1 (TGF-β1), and neutrophil infiltration.Myocardial NET burden was increased in HF patients with diabetes. High glucose triggered inflammasome activation in human neutrophils. After STZ, PAD4⁻/⁻ and WT mice developed hyperglycaemia and weight loss, yet only WT neutrophils showed increased NETosis and ASC speck formation. Only diabetic WT mice exhibited elevated IL-1β and VWF levels, impaired cardiac function, reduced exercise tolerance, and pulmonary oedema; PAD4⁻/⁻ mice were protected. Wild-type diabetic hearts and kidneys showed greater fibrosis, neutrophil infiltration, NETs, and TGF-β1 levels. Kidney injury in WT mice was reflected by albuminuria and renal fibrosis, whereas PAD4⁻/⁻ mice preserved renal function.Diabetes promotes neutrophil inflammasome activation and NETosis, driving cardiac and renal inflammation and fibrosis. Peptidylarginine deiminase 4 deficiency prevents heart failure and preserves kidney function in experimental diabetes.
Gesehen am 13.01.2026